KEMAMPUAN SISWA SMP DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI SIKAP TERHADAP MATEMATIKA - Nelly Nurmariati; Hamdani Hamdani; Dona Fitriawan (Jurnal AlphaEuclidEdu, 2023)
Mathematics can train children to think logically, systematically and as a means of honing their problem-solving skills in everyday life. In learning mathematics, students are required to study mathematics with full serousness so as to obtain good mathematics leraning outcomes. One of the factors that affect how well students learn is attitude. The attitude towards mathematics can be seen from the way students react with mathematics. So that there will be students who have a positive and negative attitude towards mathematics. This study aims to determine how student’s ability to solve problems based on student’s attitudes towards mathematics. The research subjects were 10 students of class VIII C SMP Negeri 01 Jongkat who wereinterviewed with questions about student’s attitudes towards mathematics and then selected 3 students who were positive and 3 students who were negative. The instruments used were tests and interview. The descriptive method is used in this study. Based on the results of the study, it shows that student’s attitudes towards mathematics have a positive effect on the ability to solve math problems. The more positive student’s attitudes towards mathematics will results in an increase in tsudent’s ability to solve math problem